Centenario Provincia de Neuquén : 50 viviendas (Trama)
Proyectos premiados en el marco del FONAVI. Contiene: 1° premio : Barbella, Jorge Roberto - De Raffaelli, María Beatriz - Raymundo, Claudio Augusto. 2° premio: Torcello, Horacio - Ferri, Guillermo - Maceo, Miguel - Travieso, Gustavo. 3° premio : Bertot, José Luis - Beraldi, Sergio - Gaite, Arnoldo - Gaite, Martín - Gomez Diz, Walter - Ruiz Orrice, Juan - Slivka, Eduardo - Suñer, Juan. 4° premio : Altona, Enrique - Busso, Carlos. 5° premio : Gonzalez Montaner, Humberto - Gonzalez Montaner, Luis - Macchi, José Luis - Ryan, Mark.